Advances in gene therapy for cartilage repair - Cucchiarini, Magali; Madry, Henning (Annals of Joint, 2018)
Articular cartilage defects are a common problem in joints. As articular cartilage has a limited intrinsic capability for self-repair, their clinical treatment remains problematic as none of the current therapeutic options can regenerate adult cartilage and prevent the development of osteoarthritis (OA) over the long term. Treatments based on therapeutic gene vectors typically involve approaches based on the intraarticular delivery of gene vectors or of genetically modified cells, sometimes via biocompatible materials. This review highlights the current state of gene therapy strategies for cartilage repair.